Best Practices for Writing Letters of Recommendation for Maternal-Fetal Medicine Fellowship: An Empty Scoping Review - Dotters-Katz, Sarah K.; Kirsch, Elayna; Cantrell, Sarah; Shanks, Anthony; Temming, Lorene; Gray, Beverly (American Journal of Perinatology, 2023)
Objectives Though letters of recommendation (LOR) for Maternal-Fetal Medicine (MFM) fellowship are a critical part of application process, little is known regarding best practices for writing them. This scoping review sought to identify published data outlining best practices in writing MFM fellowship LOR.Study Design Scoping review conducted using Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) and JBI guidelines. MEDLINE, Embase, Web of Science, and ERIC were searched, by professional medical librarian using database-specific controlled vocabulary and keywords representing MFM, fellowship, as well as personnel selection, academic performance, examinations, or clinical competence in 4/22. Prior to execution, the search was peer reviewed by another professional medical librarian using the Peer Review Electronic Search Strategies (PRESS) checklist. Citations imported to Covidence, dual screened by authors with disagreements resolved by discussion, and extraction performed by one author and checked by the second.Results A total of 1,154 studies were identified, with 162 removed as duplicates. Of the 992 screened, 10 imported for full-text review. None of these met inclusion criteria; four were not about fellows and six did not report on best practices for writing LOR for MFM.Conclusion No articles were identified that outlined best practices for writing LOR for MFM fellowship. The lack of guidance and published data guiding those writing LOR for MFM fellowship applicants is concerning given the importance of these as a tool used by fellowship directors in selecting applicants for interviews and ranking.Key Points
Keywords: fellowship; letters of recommendation; application; best practices